Effect of maternal and postweaning folic acid supplementation on colorectal cancer risk in the offspring. Issue 12 (11th May 2011) - Sie, Karen K Y; Medline, Alan; van Weel, Jacobine; Sohn, Kyoung-Jin; Choi, Sang-Woon; Croxford, Ruth; Kim, Young-In
Abstract : Background: Intrauterine and early life exposure to folic acid has significantly increased in North America owing to folic acid fortification, widespread supplemental use and periconceptional folic acid supplementation. The effect of maternal and postweaning folic acid supplementation on colorectal cancer risk in the offspring was investigated. Methods: Female rats were placed on a control or supplemental (2.5× the control) diet prior to mating and during pregnancy and lactation. At weaning, male pups from each maternal diet group were randomised to the control or supplemental diet (n=55 per each of the four maternal/pup diet groups) for 31 weeks and colorectal cancer was induced by azoxymethane at 5 weeks of age. At necropsy, colorectal cancer parameters as well as colorectal epithelial proliferation, apoptosis and global DNA methylation were determined in the offspring. Results: Maternal, but not postweaning, folic acid supplementation significantly reduced the odds of colorectal adenocarcinoma by 64% in the offspring (OR 0.36; 95% CI 0.18 to 0.71; p=0.003). Pups from the dams fed the control diet that were given postweaning folic acid supplementation had significantly higher tumour multiplicity and burden than other groups (p<0.05). Maternal and postweaning folic acid supplementation interacted in a manner that decreased rectal epithelial proliferation (p<0.05). Both maternal and postweaning folic acid supplementation significantly decreased DNA damage in the rectum (p<0.05). Maternal folic acid supplementation significantly increased (p=0.007), whereas postweaning supplementation significantly decreased (p<0.001), colorectal global DNA methylation. Conclusions: The data suggest for the first time that maternal folic acid supplementation at the level equivalent to the average postfortification total folate intake in North America and to that recommended to women at reproductive age protects against the development of colorectal cancer in the offspring. This protective effect may be mediated in part by increased global DNA methylation and decreased epithelial proliferation and DNA damage in the colorectum.